2020
DOI: 10.12973/ijem.6.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Computer Programming Self-Efficacy’s Prediction towards the Computational Thinking Skills of the Gifted and Talented Students

Abstract: <p style="text-align: justify;">The study's goal was to examine the correlation between the computer programming self-efficacy and computational thinking skills of gifted and talented students. The capacity of the computer programming self-efficacy of gifted and talented students to predict their computational thinking skills were also examined. The relational screening model has been implemented in the research. The participants of the study were composed of 106 secondary school gifted and talented stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…In the literature, there are studies on non-cognitive factors that support the results of this study. It was found that there is a moderate significant relationship between CPA and CPSE (Çoban, Korkmaz, Çakır & Erdoğmuş, 2020); and a moderate significant relationship between CT and CPSE (Durak, Yılmaz, & Yılmaz, 2019) and CPSE predicted CT significantly (Avcu & Ayverdi, 2020). The importance of the data obtained within the scope of this study is that the CPSE and CPA variables, which come to mind as the non-cognitive factor when it comes to CT, are considered together for the middle school students, and this study reveals the order of their importance.…”
Section: Discussion Of Findingsmentioning
confidence: 67%
See 1 more Smart Citation
“…In the literature, there are studies on non-cognitive factors that support the results of this study. It was found that there is a moderate significant relationship between CPA and CPSE (Çoban, Korkmaz, Çakır & Erdoğmuş, 2020); and a moderate significant relationship between CT and CPSE (Durak, Yılmaz, & Yılmaz, 2019) and CPSE predicted CT significantly (Avcu & Ayverdi, 2020). The importance of the data obtained within the scope of this study is that the CPSE and CPA variables, which come to mind as the non-cognitive factor when it comes to CT, are considered together for the middle school students, and this study reveals the order of their importance.…”
Section: Discussion Of Findingsmentioning
confidence: 67%
“…These studies generally deal with variables related to cognitive structure. However, affective variables are also important for CT skills (Román-González, Pérez-González & Jiménez-Fernández, 2017;Román-González, Pérez-González, Moreno-León, & Robles, 2018) and it is recommended to establish regression models in the future studies to predict CT skills (Avcu & Ayverdi, 2020). In the literature review, the first study that comes to mind about the CT skills at the middle school level, CPSE (Computer Programming Self-Efficacy) and CPA (Computer Programming Attitude) were not studied in the same experiment together.…”
Section: Introductionmentioning
confidence: 99%
“…As future leaders and drivers of the K-economy, students need to prepare for innovation to be ready for the K-economy. Students need to foster creativity and innovation (Adijaya et al, 2023) to prepare innovations for the K-economy to develop creativity and innovation skills (Avcu & Ayverdi, 2020), which are essential in the K-economy that focuses on developing new products and services (Larraz et al, 2017;Siddiqui & Afzal, 2022). Then, they must increase competitiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Through research on self-efficacy as learning motivations factor, many scholars have demonstrated their relationship. For example, Emre and Ayverdi [13]; Durak et al [14]; Gorson and O'Rourke [15], had state that individuals with a high perception of self-efficacy on a particular situation strive to accomplish a task. They do not easily give up and are persistent and patient.…”
Section: Figure 1 Deduction Approachmentioning
confidence: 99%